Lengths of inpatient stay and sick leave of patients with mental diseases: disorder-specific effects of flexible and integrated treatment programs in Germany - Baum, Fabian; Schmitt, Jochen; Seifert, Martin; Kliemt, Roman; Kubat, Denise; March, Stefanie; Häckl, Dennis; Pfennig, Andrea; Swart, Enno; Neumann, Anne (Translational psychiatry, 2022)
Mental disorders pose a worldwide growing public health burden. One of the major challenges for healthcare systems remains to respond to the need of patients with mental disorders for continuous and flexible treatment. The EVA64 study evaluates novel programs of flexible and integrative treatment (FIT) in hospitals. This manuscript presents results from the evaluation of FIT hospitals in comparison to hospitals from regular routine care. In addition to data from adult patients, we also present data from affiliated child and adolescent psychiatric wards employing FIT programs. Using comprehensive claims data, primary outcomes are the utilization of inpatient care and sick leave for a priori defined clusters of mental disorders. We stratify between patients already under treatment (ongoing treatment) and patients with incident treatment cases (initial treatment) at the point of inclusion in the study. In the initial treatment group, we found a significant reduction in the length of inpatient stay of 4.1 days in FIT hospitals compared to routine care. While patients with mood affective disorders (−1.8 days) and patients with neurotic, stress-related, and somatoform disorders (−3.6 days) showed an even stronger effect of the reduction of inpatient lengths of stay, the effect was significantly weaker in patients with mental and behavioral disorders due to use of alcohol (+3.3 days). Regarding the duration of sick leave, we found no significant treatment effect of FIT programs compared to routine care. In the ongoing treatment group of adult patients, we found a significantly lower utilization of inpatient treatment by 1.3 days as well as a shorter duration of sick leave by 4.3 days in FIT hospitals compared to routine care. In the cohort of children and adolescent patients, we also did not observe a significant treatment effect in either the initial treatment group or the ongoing treatment group. Registration: this study was registered in the database “Health Services Research Germany” (trial number: VVfD_EVA64_15_003713).